2008
DOI: 10.1136/bjo.2008.139329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antiglaucoma fixed combination therapy versus unfixed components in reducing intraocular pressure: a systematic review

Abstract: Fixed combination therapies are equally safe and effective at lowering IOP as their non-fixed components administered concomitantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
16
0
6
Order By: Relevance
“…A systematic review involving seven randomized controlled trials on various fixed combination with 0.5% timolol; travaprost, latanoprost, dorzolamide and brimonidine found that the concomitant treatment with individual drug has the edge in efficacy. However, the difference failed to exert pre-determined non-inferiority measure of ≤1.5mmHg upper confidence limit (Cox et al, 2008). Similar outcome is also noted in another systematic review and metanalysis of 29 studies involving fixed combination of prostaglandin analogs and timolol (Webers et al, 2010).…”
Section: Fixed Combinationsupporting
confidence: 57%
“…A systematic review involving seven randomized controlled trials on various fixed combination with 0.5% timolol; travaprost, latanoprost, dorzolamide and brimonidine found that the concomitant treatment with individual drug has the edge in efficacy. However, the difference failed to exert pre-determined non-inferiority measure of ≤1.5mmHg upper confidence limit (Cox et al, 2008). Similar outcome is also noted in another systematic review and metanalysis of 29 studies involving fixed combination of prostaglandin analogs and timolol (Webers et al, 2010).…”
Section: Fixed Combinationsupporting
confidence: 57%
“…Ao disponibilizar duas medicações de ações complementares em um mesmo frasco, elas têm a vantagem de facilitar a posologia, aumentar a aderência e reduzir a PIO de maneira eficiente. (6) Diversos estudos mostraram a segurança clínica e a eficácia destas associações fixas para o tratamento clínico do glaucoma e da hipertensão ocular. (6) Do ponto de vista econômico, Martinez et al, na Espanha, concluíram que a associação fixa BT seria a melhor opção.…”
Section: Discussionunclassified
“…(6) Diversos estudos mostraram a segurança clínica e a eficácia destas associações fixas para o tratamento clínico do glaucoma e da hipertensão ocular. (6) Do ponto de vista econômico, Martinez et al, na Espanha, concluíram que a associação fixa BT seria a melhor opção. Nesse estudo, o custo de cada percentual de redução da PIO ao final de 3 meses foi de 5,34 euros para BT, 5,40 euros para LT e 5,45 euros para TT.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There may be several mechanisms for loss of the effectiveness of these monotherapeutic agents; some include tachyphylaxis and disease progression [4]. This loss may be resolved by using combination of different classes of drugs which aims at different targets or pathways to combat the disease with minimal adverse effects [5]. The combination therapy could also improve tolerability because two compounds may be employed below their individual dose thresholds [6].…”
mentioning
confidence: 99%